Kajian Etnobotani Pangan Fungsional: Menggali Pengetahuan Lokal Masyarakat Arjowilangun untuk Ketahanan Pangan Berkelanjutan - Anis Ferlina Nur Aini; Aulia Triana Devi; Fashya Auliyya Putri Yuswanda; Sururin Masfufah; Fahrul Ghani Muhaimin; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
This study aims to identify, document, and analyze the quantitative ethnobotanical index of functional food plants in Arjowilangun Village, Malang Regency. The study used a sequential exploratory design method. The qualitative stage was carried out through observation, documentation, and interviews using purposive sampling and snowball sampling techniques, then continued with the quantitative stage using questionnaires to test and strengthen the interview data. Quantitative ethnobotanical analysis was carried out using the Informant Consensus Factor (ICF), Relative Frequency Factor (RFC), Species Use Value (FUV), and Plant Part Use Value (PPUV) indices. The results of the study recorded 21 plant species from 15 families that are used as functional foods with a variety of habitus such as trees, herbs, bushes, and shrubs. The most widely used plant parts are rhizomes, tubers, leaves, fruits, flowers, and stems. Plants are used as food and traditional medicine through various processing techniques, such as boiling, pounding, stir-frying, and making herbal drinks. The ethnobotanical index analysis results showed an ICF of 0.99, indicating a very high level of community agreement regarding the use of functional food plants. Some of the species with the highest utilization rates were turmeric, galangal, ginger, lemongrass, cassava, and bay leaves. The conclusions of this study indicate that the people of Arjowilangun Village possess rich local knowledge regarding the use of functional food plants, with the dominant use of the leaves. There is also a high community consensus regarding the use of certain species that have the potential to support the conservation of biological resources and local food security.